Immune Regulator Retinoic Acid-Inducible Gene I (RIG-I) in the Pathogenesis of Cardiovascular Disease - Wang, Hao; Yin, Jie; Gu, Xinyan; Shao, Wenhui; Jia, Zhanjun; Chen, Hongbing; Xia, Weiwei (Frontiers in Immunology, 2022)
Retinoic acid-inducible gene I (RIG-I) is a cytosolic pattern recognition receptor that contains two CARD domains, an RNA helicase-DEAD box domain, and a C-terminal domain. RIG-I initiates antiviral innate immunity by recognizing exogenous viral RNAs/DNAs. However, some studies have reported that RIG-I activation leads to damage in various organs and tissues in diverse circumstances. Recent studies have shown that RIG-I is involved in cancer, lupus nephritis, immunoglobulin A nephropathy, Crohn's disease, and atherosclerosis. These reports indicate that RIG-I not only participates in antiviral signaling pathways but also exerts an influence on non-viral infectious diseases. RIG-I is widely expressed in immune and non-immune cells including smooth muscle cells, endothelial cells, and cardiomyocytes. A succinct overview of RIG-I and its signaling pathways, with respect to the cardiovascular system, will aid in the development of novel therapeutics for cardiovascular diseases. In this review, we summarize the structure, activation, signaling pathways, and role of RIG-I in cardiovascular diseases.